Association of ulcerative colitis and acute gastroenteritis with prostate specific antigen: results from National Health and Nutrition Examination Survey from (2009 to 2010) and Mendelian randomization analyses - Li, Hongxiao; Zheng, Jiefang; Dong, Weimin; Huang, Yiqiao; Su, Zhengming; Jiang, Xianhan (Frontiers in Nutrition, 2023)
Background An increasing number of studies have demonstrated that gastrointestinal inflammation may increase prostate cancer risk and raise the prostate-specific antigen (PSA) level. However, the association between ulcerative colitis (UC) and acute gastroenteritis (AGE) with PSA remains unclear and complicated. Herein, we evaluated the relationship between UC and AGE with PSA concentration using the National Health and Nutrition Examination Survey (NHANES) database and Mendelian randomization (MR) analyses. Materials and methods A total of 1,234 participants fit into the study after conducting the screening based on the NHANES survey conducted from 2009 to 2010. UC and AGE were the independent variables, and PSA was the dependent variable. Weighted multiple linear regressions were utilized to estimate the association of UC and AGE with PSA concentration. To detect the causal relationship between UC and AGE with PSA, a two-sample Mendelian randomized analysis was conducted. Results After controlling for all covariates, PSA (log2 transform) concentrations in the UC group were increased by 0.64 (0.07, 1.21). AGE was not independently associated with PSA levels after adjusting potential confounders. In patients with coronary artery disease, AGE promotes elevated PSA (log2 transform) concentrations (β = 1.20, 95% CI: 0.21–2.20, p < 0.001). Moreover, an IVW MR analysis indicated that genetically predicted UC was associated with increased PSA, and that AGE was not associated with PSA. Conclusion This study indicated that a positive causal association exists between UC and the PSA level. However, there is no evidence to support the relationship between AGE and the PSA level.